Deep vein thrombosis of lower limbs in patients with COVID-19 - Saliba Júnior, Orlando Adas [UNESP]; Alves, Ana Flávia de Jesus; Matarazzo, Camila; Gonçalves, Gabriela Teixeira; Sobreira, Marcone Lima [UNESP] (FapUNIFESP (SciELO), 2023)
As knowledge has accumulated, COVID-19 has come to be considered a disease of the respiratory system that can also cause multisystemic involvement. This study analyzed the prevalence of deep venous thrombosis (DVT) in the lower limbs of patients with COVID-19 by conducting an integrative review of the literature published from 2019 to 2022. The procedures involved in article selection were identification of keywords, definition of the search strategy, consultation of databases, and exclusion of duplicate articles and others that did not meet the review objectives. Exclusion of articles was based on the following exclusion criteria: articles on arterial vascular complications involving the lower limbs, laboratory experiments, cases reports describing venous and arterial complications involving other sites, and articles unrelated to the outcome of interest: DVT. A total of 284 articles were identified, 42 of which were included. There was considerable variability in the prevalence of DVT among patients with COVID-19 (range: 0.43 to 60.87%). The findings suggest that occurrence of DVT in patients with COVID-19 is associated with disease severity.
Trombose venosa profunda de membros inferiores em pacientes com covid-19
Keywords: anticoagulant; SARS-CoV-2; thromboembolism